Economics of Bulk Storage Techniques: Maize and Cowpea Storage in Ghana. (16th July 2022) - Bidzakin, John K.; Yeboah, Osei; Sugri, Issah; Graves, Anil; Awunyo-Vitor, Dadson
Abstract : High postharvest loss is one of the major challenges faced by farmers in many African countries in their efforts to achieve food and nutrition security. Several postharvest techniques have been developed and introduced to farmers aimed at reducing food losses. This study evaluated the economic viability of four such grain storage techniques using capital budgeting techniques. Two grain protectants were applied at recommended rates in three treatment combinations to jute sacks, PICS sacks, polytanks, and poly sacks at different treatment levels and at different discount rates. Under maize storage, the net present value of all treatments yielded positive net returns. The polytank technique proved to be the most economically viable storage technique, followed by PICS and then jute sacks. Under cowpea storage, polytank proved to be the most viable, followed by PICS. This is consistent under replacement chain method and equivalent annual annuity under the three different discount rates used. Cowpea is best stored in polytanks and PICS sacks. Polytank is recommended as the most economically viable storage technique for both maize and cowpea storage. PICS is also recommend for both maize and cowpea storage. However, jute sacks and poly sacks are not suitable for cowpea storage even under chemical treatment, especially under long-term storage (over 6 months). The choice of storage technique should consider the commodity under consideration.